2018
DOI: 10.1186/s12889-018-5460-3
|View full text |Cite
|
Sign up to set email alerts
|

Altruism, Scepticism, and collective decision-making in foreign-born U.S. residents in a tuberculosis vaccine trial

Abstract: BackgroundThe current vaccine against tuberculosis, BCG, is effective when given in most TB-endemic countries at birth but has diminished efficacy against pulmonary TB after 15–20 years. As a result, new booster vaccines for adolescents and adults are being developed to realize the World Health Organization target of global elimination of TB by 2035. Multiple TB candidates thus are in active clinical development.MethodsOne of these, DAR-901, is advancing in human clinical trials. These clinical trials are cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Participants were willing to take part as long as they were provided with adequate information to make an informed decision. Other participants indicated that not only would they participate for their own sake and monetary compensation but also for the love of others and to contribute to science, motives also expressed by studies in other LMIC settings [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Participants were willing to take part as long as they were provided with adequate information to make an informed decision. Other participants indicated that not only would they participate for their own sake and monetary compensation but also for the love of others and to contribute to science, motives also expressed by studies in other LMIC settings [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Participants were willing to take part as long as they were provided with adequate information to make an informed decision. Other participants indicated that not only would they participate for their own sake and monetary compensation but also for the love of others and to contribute to science, motives also expressed by studies in other LMIC settings [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…These include concerns about privacy, language barriers, a lack of belief in the benefit of research to community, research procedures such as informed consent process which are unfamiliar or culturally inappropriate, and study working hours or locations which are inconvenient for participants. 9,[17][18][19][20][21][22][23] There are additional structural level barriers to participation in research that likely also hinder research participation among marginalized populations, including differential access to health care or other services where recruitment might take place, the legacy of research misconduct and human rights abuses associated with studies such as the Tuskegee Syphilis Study, power imbalances between researchers and participants, including beliefs researchers gain more from research than the communities that participate in their studies, and specific to immigrants, fear that uptake of health services or research participation might have negative immigration-related consequences. 9,17,19,22,[24][25][26][27][28][29][30][31] Some of these barriers have been successfully addressed by engaging community advisory boards, undertaking other forms of community engagement such as health fairs or working with community leaders, ethnic and linguistic "matching" of recruiters to the population of interest, making the consent process transparent and straightforward, providing hours and locations that are convenient, providing translated information and interpreters for those with low English proficiency, and ensuring that research participants are adequately compensated for their time.…”
Section: Discussionmentioning
confidence: 99%
“…9,17,19,22,[24][25][26][27][28][29][30][31] Some of these barriers have been successfully addressed by engaging community advisory boards, undertaking other forms of community engagement such as health fairs or working with community leaders, ethnic and linguistic "matching" of recruiters to the population of interest, making the consent process transparent and straightforward, providing hours and locations that are convenient, providing translated information and interpreters for those with low English proficiency, and ensuring that research participants are adequately compensated for their time. 9,20,21,23,32 Recruitment practices to address some of the more structural-level barriers have been less well documented in the literature. Recruiting participants in the community or via community-based organizations that serve specific populations rather than at facilities has been successful in many instances.…”
Section: Discussionmentioning
confidence: 99%